Perancangan dan Pengembangan Alat Pengukur UV dan Pelacak Surya Dual-Axis Berbasis IoT untuk Optimalisasi Pemantauan Indeks UV Secara Real-Time - Dwi Agustian; Ilham Muthahhari; Valiant Yuvi Syahreza; Anton Widodo; Muchamad Rizqy Nugraha; Edward Trihadi (Yayasan Kita Menulis - JoCPES, 2025)
The ultraviolet (UV) radiation emitted by the sun has both positive and negative impacts on human life. Excessive exposure to UV rays can lead to various health issues, such as skin cancer and cataracts. Therefore, UV radiation monitoring becomes crucial, especially in the face of climate change, which may increase the intensity of UV radiation due to the depletion of the ozone layer. This study aims to design an Internet of Things (IoT)-based UV index monitoring system, equipped with a dual- axis solar tracker to optimize UV index measurements. The system utilizes the ESP32 microcontroller as the main processing unit, the UVM-30A sensor to detect UV radiation, and the DS3231 Real Time Clock (RTC) module for time synchronization. UV index data is displayed in real-time through a Liquid Crystal Display (LCD) screen and the Blynk platform for easy remote access. Test results show that the system performs well, with a low relative error compared to UV index data from the reference site uvindex.app. This system provides an innovative solution for efficient and real-time UV index monitoring, which can increase public awareness about the dangers of UV radiation.